Alternative consent models for comparative effectiveness studies: Views of patients from two institutions. Issue 2 (2nd April 2016) - Kass, Nancy; Faden, Ruth; Fabi, Rachel E.; Morain, Stephanie; Hallez, Kristina; Whicher, Danielle; Tunis, Sean; Moloney, Rachael; Messner, Donna; Pitcavage, James
ABSTRACT: Background : Informed consent requirements generally require a lengthy process and signed documentation for patients to participate in clinical research. With growing interest in comparative effectiveness research (CER), whereby patients receive approved (nonexperimental) medicines for their medical condition, questions have been raised whether the same consent requirements should apply. Little input from patients has been part of these debates.Methods : We conducted two "deliberative engagement sessions" with patients from Johns Hopkins Community Physicians (JHCP) and Geisinger Health System (GHS). Full-day sessions introduced participants to two different CER designs (observational vs. randomized) comparing two antihypertensive medications and three disclosure or consent approaches: Opt-In, Opt-Out, and "General Approval." Sessions consisted of presentations and extensive discussion at small group tables. Pre- and posttest surveys were completed by participants before and after all-day discussions measuring attitudes about research and about each of the three disclosure/consent options.Results : One hundred thirty-seven adults over age 40 years participated. Attitudes were similar between JHCP and GHS. Participants strongly preferred Opt-In or Opt-Out consent options to General Approval for both observational and randomized designs. For the randomized CER study, 70% liked Opt-In, 65% liked Opt-Out, and 40% liked General Approval. In discussing disclosure/consent options, patients cared most about choice, information, privacy and confidentiality, quality of the research, trust, respect, and impact of the study on patient care.Conclusions : The majority of participants from two different types of health systems liked both Opt-In and Opt-Out approaches for observational and randomized designs for low-risk CER. There were no posttest differences in the proportion liking Opt-In versus Opt-Out. Patients in this study wanted to be told about research and have a choice, but were very open to such disclosures being streamlined. Policymakers may find patients' views about what matters to them in the context of consent and CER relevant.